Objective evaluation of tongue diagnosis ability using a tongue diagnosis e-learning/e-assessment system based on a standardized tongue image database - Segawa, Makoto; Iizuka, Norio; Ogihara, Hiroyuki; Tanaka, Koichiro; Nakae, Hajime; Usuku, Koichiro; Yamaguchi, Kojiro; Wada, Kentaro; Uchizono, Akihiro; Nakamura, Yuji; Nishida, Yoshihiro; Ueda, Toshiko; et al. (Frontiers in Medical Technology, 2023)
Background: In Kampo medicine, tongue examination is used for the diagnosis of the pathological condition “Sho,” but an objective evaluation method for its diagnostic ability has not been established. We constructed a tongue diagnosis electronic learning and evaluation system based on a standardized tongue image database. Purpose: To verify the practicality of the evaluation system by evaluating the tongue diagnosis ability of 15 Kampo specialists (KSs) and clarify the actual condition of the tongue diagnosis ability of the aforementioned group of experts. Methods: In the first study, we analyzed the answer data of 15 KSs in an 80-question tongue diagnosis test that assesses eight aspects of tongue findings and evaluated (i) test score, (ii) test difficulty and discrimination index, (iii) diagnostic consistency, and (iv) diagnostic match rate between KSs. In the second study, we analyzed the answer data of a tongue color discrimination question asked to 107 medical staff and 56 students and evaluated the correct answer rate and test difficulty. Result: In the first study, the average test score was 62.2±10.7 points. Twenty-eight questions were difficult (correct answer rate, <50%), 34 were moderate (50%-85%), and 18 were easy (≥85%). Regarding intra-rater reliability, the average diagnostic match rate of five KSs involved in database construction was 0.66±0.08, and as for inter-rater reliability, the diagnostic match rate between the 15 KSs was 0.52 (95% confidence interval, 0.38–0.65) for Gwet’s agreement coefficient 1, and the degree of match rate was moderate. In the second study, the difficulty level of questions was moderate, with a correct rate of 81.3% for medical professionals and 82.1% for students. The discrimination index was good for the medical staff (0.35) and poor for the students (0.06). Among medical professionals, the correct answer group of this question had a significantly higher total score of the Kampo common test than the incorrect answer group (85.3±8.4 points vs. 75.8±11.8 points, p <0.01). Conclusion: This system can objectively evaluate tongue diagnosis ability, and has high practicality and reliability. Utilizing this system can be expected to contribute to the improvement of learners' tongue diagnosis ability and standardization of tongue diagnosis.